Study on prevalence of hypothyroidism in ST segment elevation myocardial infarction - K. R., Sreevidya; B., Renymol (International Journal of Research in Medical Sciences, 2017)
Background: Both subclinical and overt hypothyroidism have effects on myocardial contractility and cardiovascular haemodynamics. In addition, changes in lipids, low levels of inflammation, elevated homocysteine etc. contribute to accelerated atherosclerosis and increased cardio vascular mortality and morbidity in hypothyroidism. In this study, we tried to find out the prevalence of hypothyroidism in patients admitted with acute ST elevation myocardial infarction. We also tried to assess the BMI, diastolic BP and lipid profile of these patients. Methods: A cross sectional study was done among patients admitted with ST elevation myocardial infarction in Coimbatore Medical College, Coimbatore, Tamil Nadu, India. We collected information on BMI, blood pressure, lipid profile and thyroid function of these patients. Results: The prevalence of hypothyroidism was found to be 14% in patients admitted with ST elevation MI. Hypothyroidism was three times more common in women. Patients with hypothyroidism was found to have higher BMI, elevated total cholesterol, triglycerides and LDL which was statistically significant. Higher prevalence of diastolic hypertension was also seen among hypothyroid patients. Conclusions: Thyroid hormone has various actions on heart. Hypothyroidism has increased cardiovascular morbidity and mortality. The associated risk factors like obesity, hyperlipidaemia and diastolic hypertension contribute to this. Patients with coronary artery disease should be screened for hypothyroidism.